The Treatment of Cultural Services in Central American Countries’ Preferential Trade Agreements - Gagné, Gilbert; Nycz, Cassandre (Latin American Journal of Trade Policy, 2023)
Cultural products (including goods and services) encompass visual, performing and literary arts, as well as newspapers, magazines, books, films, video and music recordings, radio and television, either in traditional or digital format. To the extent that they reflect the cultural identities of states, their treatment in international trade has been debated as to whether, or the extent to which, they should be exempted from trade obligations. The proliferation of preferential trade agreements and of digital platforms has rendered the debate ever more salient. The article summarizes the provisions on cultural services in Central American countries’ preferential trade agreements and discusses the scope of these provisions, in light of the cultural policy measures involved and states’ ability to pursue cultural policies. The countries considered are those belonging to the Central American Common Market, namely Costa Rica, El Salvador, Guatemala, Honduras, Nicaragua, and Panama. These countries share some characteristics which make them worth considering in regard to the trade and culture debate. They also vary widely with respect to the number and scope of their commitments and/or exceptions relating to culture within the preferential trade agreements to which they are parties. In turn, such significant variations are primarily attributable to the importance each Central American country attaches to the protection of its cultural sector.